Computing with Spatial Trajectories - Zheng, Yu.; Zhou, Xiaofang; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
none
Part I Foundations -- Trajectory Preprocessing -- Trajectory Indexing and Retrieval -- Part II Advanced Topics -- Uncertainty in Spatial Trajectories -- Privacy of Spatial Trajectories -- Trajectory Pattern Mining -- Activity Recognition from Trajectory Data -- Trajectory Analysis for Driving -- Location-Based Social Networks: Users -- Location-Based Social Networks: Locations.
Keywords: Computer science; Database management; Data mining; Information storage and retrieval systems; Computer vision; Optical pattern recognition; Geographical information systems; Computer Science; Database Management; Geographical Information Systems/Cartography.; Data Mining and Knowledge Discovery; Computer Imaging, Vision, Pattern Recognition and Graphics; Pattern Recognition; Information Storage and Retrieval